Good corporate governance dan Ukuran Perusahaan Sebagai Stimulus Di Lakukannya Tax Management - yunita valentina kusufiyah (JURNAL PUNDI, 2018)
The largest state revenue comes from tax revenues. This is evident from the data of the Central Bureau of Statistics in 2016 as much as 86.16% of state revenue derived from tax revenue. For the company, the tax is a expenses that must be paid so needed a strategy in doing the efficiency of the tax expenses (the tax savings). One such strategy is tax management. To perform a good tax management then it takes the implementation of good governance in a company. Another variable that becomes the stimulus of Tax Management is the size of the company. This study examines Good corporate governance and Corporate Size as Stimulus in Tax Management. The research was conducted at a banking company listed on the Indonesia Stock Exchange. Research methodology used in this research is regression analysis that is linear regression analysis. The findings in this study are institutional ownership, the proportion of independent board of commissioners has a positive and significant influence on tax management while the audit committee has no influence on tax management. Company size has a significant negative effect on tax management Keywords : Good Corporate Governance, size, Tax Managemet